2008
DOI: 10.1002/pon.1323
|View full text |Cite
|
Sign up to set email alerts
|

Adolescent's stress responses and psychological functioning when a parent has early breast cancer

Abstract: When mothers have breast cancer, a substantial minority of their adolescent children have psychological and stress response-related problems linked with poor family functioning. These results argue in favour of a family-oriented approach to psychological support of breast cancer patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
135
4
8

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(154 citation statements)
references
References 35 publications
7
135
4
8
Order By: Relevance
“…This intervention confirms the previous studies about the importance of an open communication to support children to face with cancer's diagnosis [5,10,[14][15][16]. The project highlights the advantages of direct engagement of children in the communication of the parent's illness to improve the relationships within the family.…”
Section: Discussionsupporting
confidence: 74%
“…This intervention confirms the previous studies about the importance of an open communication to support children to face with cancer's diagnosis [5,10,[14][15][16]. The project highlights the advantages of direct engagement of children in the communication of the parent's illness to improve the relationships within the family.…”
Section: Discussionsupporting
confidence: 74%
“…Maternal breast cancer-specific distress was measured using 8 items of the Revised Impact of Event Scale, to parallel the Child Impact of Events Scale (Cronbach's α = 0.88). [47][48][49][50][51][52][53] …”
Section: Methodsmentioning
confidence: 99%
“…[47][48][49][50] Both have been used to evaluate intrusion and avoidance, as indices of cancerspecific "distress." [51][52][53] Daughter performance of health and risk behaviors were assessed with items from the Youth Risk Behavior Survey, 53 which has been used to track health and risk behaviors of >10 000 youths. 54,55 Daughter perception of breast cancer risk was assessed with a single item adapted from a longitudinal study of families at hereditary risk for breast cancer.…”
Section: Methodsmentioning
confidence: 99%
“…Cognitive development and psychosocial difficulties (Osborn, 2007;Visser et al, 2007;Edwards et al, 2008) were not analysed as the focus was for content evidencing children's conceptualisation of cancer irrespective of any specific age. Moreover, an age specific analysis of the type of children's responses may be inconclusive from only 22 children because children participants had different carer roles, interests and skill sets.…”
Section: Methodsmentioning
confidence: 99%
“…Even though Malaysia recorded lower number of children, the ratio was higher at 2.5 children per household (Banci Penduduk dan Perumahan Malaysia, Jabatan Perangkaan, 2013). Visser et al (2004), Visser et al (2007), Osborne (2007) and Edwards et al (2008) reported that parental cancer had a range of consequences from the aspect of children's functioning and psychosocial difficulties. Anxiety, fear and uncertainty were common emotional distresses (Kornreich et al, 2008;Fourie, 2008;Buchwald, 2007;Watson, 2006).…”
mentioning
confidence: 99%